KREATIVITAS GURU PAI DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PAI - Mutmainna Binti Makmur , (UNISAN JURNAL, 2024)
The motivation behind this examination is to find out and comprehend the job of Islamic Strict Training Educators to expanding understudies' advantage in learning in Islamic Strict Schooling subjects. This examination utilizes a subjective exploration strategy which occurred at the Al-Wahdah Bombana Coordinated Islamic Center School. Scientists led organized interviews and unstructured meetings with asset people (SMPIT Islamic Strict Instruction instructors) upheld by documentation information and direct perception. As a finding in this examination, in particular the presence of a unique job in regards to the survey of the job of educators to expanding understudies' advantage in learning in PAI subjects at Al-Wahdah Coordinated Islamic Confidential Center School, Bombana, it tends to be reasoned that In light of the consequences of information examination and conversations that have been depicted in the sections beforehand, the ends in this exploration can be planned as follows. 1. Execution of learning the executives in working on the nature of sewing graduates at the Anisya course and preparing organization which comprises of arranging, carrying out and assessing advancing overall has been completed well. 2. There are a few supporting elements for carrying out learning the executives in working on the nature of graduates at Al-Wahdah Bombana Coordinated Islamic Confidential Center School, for example, great help from the public authority, the presence of two adaptable learning programs, proficient educators, dynamic in the field of virtual entertainment, great offices and complete, as well as an essential area. Factors hindering the execution of learning the board in working on the nature of graduates at Al-Wahdah Bombana Coordinated Islamic Confidential Center School include: there are still educators who have not been confirmed, the ages and foundations of understudies are assorted, there are understudies who have gone through affirmation. certificate. not in every case following preparation to the end, and absence of understudy discipline..